ISU DAN REALITAS DI BALIK TINGGINYA ANGKA CERAI-GUGAT DI INDRAMAYU - Abdul Jamil; Fakhruddin Fakhruddin (Harmoni, 2015)
Many assumptions that divorce in Indramayu are the highest number in Indonesia nowadays. It is also considered as a culture. The causes of divorce are polygamy, low education, oversea migrant worker, and early marriages. Data from religious court shows that the number of wife-initiated divorce in Indramayu is relatively high. In 2014, the number of wifeinitiated divorce is 72% while husbandinitiated divorce is 28% in Indramayu. The result shows that divorces undertaken by wives are caused some factors such as the intensity of the problem (problem severity ) faced by wife, support from their parents, psychological suffering after divorce that they feel happier with their divorce status, and the experience from their family so they understand every step in conducting wife-initiated divorce. The greatest impact of divorce is psychological suffering which they will be disappointed towards marriage. The research concludes that the current institution that mediates a divorce in Indramayu is Lebe because KUA (Religious Affairs Office), BP4 (Marriage Counseling Agency) and PA (Religious Court) are relatively ineffective.